Black garlic melanoidins prevent obesity, reduce serum LPS levels and modulate the gut microbiota composition in high-fat diet-induced obese C57BL/6J mice. Issue 11 (5th November 2020) - Wu, Jianfu; Liu, Yanan; Dou, Zishan; Wu, Tao; Liu, Rui; Sui, Wenjie; Jin, Yan; Zhang, Min
Abstract : Black garlic MLDs fermented in the colon, produced SCFAs and modulated gut microbiota composition, thereby protected against hepatic lipid accumulation, insulin resistance, and inflammation partly. Abstract : The objective of this study is to assess the potential anti-obesity effects of black garlic melanoidins (MLDs) and gut microbiota changes in an animal model, hypothesizing that the effects of oral administration of MLDs can be partially mediated by the modulation of intestinal microbiota via inhibiting the formation of lipopolysaccharides (LPS) and promoting the production of short-chain fatty acids (SCFAs). The effects of MLDs in C57BL/6J mice with high-fat diet (HFD)-induced obesity were investigated for 12 weeks with low (50 mg kg −1 day −1 ), medium (100 mg kg −1 day −1 ) and high (200 mg kg −1 day −1 ) doses. The results indicated that oral administration of MLDs markedly reduced high fat diet-induced weight gain and white adipose tissue weights and reversed glucose tolerance, especially at high doses. Besides, MLDs could alleviate dyslipidaemia, significantly suppress hepatic lipid accumulation and steatosis and effectively ameliorate lipid metabolism. The plasma LPS reduced significantly and the SCFAs increased in a dose-dependent manner. The MLDs could down-regulate the expression of fatty acid synthase (FAS) and interleukin-6 (IL-6) and up-regulate the expression of adipose triacylglyceride lipase (ATGL) and hormone sensitive lipase (HSL) in adipose tissues and livers at mRNA levels. Moreover, after the oral administration of MLDs, the intestinal microbial environment improved in the sense that bacterial diversity and richness increased. Intervention with MLDs modified the gut microbiota in mice with HFD-induced obesity, increasing the number of SCFA-producing bacteria ( Bacteroidaceae ) and reducing opportunistic pathogens ( Enterobacteriaceae and Desulfovibrionaceae ). An increased abundance of other probiotics including Lactobacillaceae and Akkermansiaceae was also observed. In conclusion, MLDs could improve glucose tolerance, induce the production of SCFAs and inhibit the production of endotoxin LPS, most likely mediated by modulating the gut microbiota. Therefore, it seems that MLDs exhibit anti-obesity effects and might be used as potential agents against obesity.